Analysis of Literacy Learning Methods in the Process of Forming a Conceptual Framework for Student Final Projects - Utik Kuntariati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Literacy learning at this time is very important because it can help students to think more critically and be able to think in a structured way. The literacy learning method is a method that invites students to think conceptually in their learning activities in class. The derivatives of this learning system include thinking, reading, and writing. The tendency problem encountered by students when compiling their final assignment is not being able to harmonize these three aspects, so a learning method with better content is needed for students to be able to complete their final assignment comfortably. The object of this study is the effectiveness of the literacy learning method for students. The method in this study uses a qualitative approach to data analysis with data triangulation. The results in this study are that the implementation of literacy learning methods must be carried out repetitively so that students are able to describe patterns of thinking, reading, and writing.